2011
DOI: 10.1121/1.3640841
|View full text |Cite
|
Sign up to set email alerts
|

Focusing of longitudinal ultrasonic waves in air with an aperiodic flat lens

Abstract: Modeling and experimental results of an ultrasonic aperiodic flat lens for use in air are presented. Predictive modeling of the lens is performed using a hybrid genetic-greedy algorithm constrained to a linear structure. The optimized design parameters are used to fabricate a lens. A method combining a fiber-disk arrangement and scanning laser vibrometer measurements is developed to characterize the acoustic field distribution generated by the lens. The focal spot size is determined to be 0.88 of the incident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…The phase through the electronic circuit is tunable as well, and it is an additional degree of freedom usable in some applications. For example, it can be used to implement unidirectional acoustic lenses by varying the phase delay through each cell in the same way reciprocal passive metamaterial lenses are designed [1][2][3][4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase through the electronic circuit is tunable as well, and it is an additional degree of freedom usable in some applications. For example, it can be used to implement unidirectional acoustic lenses by varying the phase delay through each cell in the same way reciprocal passive metamaterial lenses are designed [1][2][3][4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the extended range of material parameters provided by metamaterials has lead to the implementation of devices such as acoustic lenses [1][2][3][4][5][6] , or even exotic structures designed using coordinate transformation methods 7,8 . Recently, significant attention has been given to unidirectional devices that pass acoustic energy in only one direction [9][10][11][12][13][14][15] and therefore mimic the general behaviour of diodes in the microwave regime, and Faraday rotator media in the optical domain.…”
mentioning
confidence: 99%
“…By shaping the pump ultrasound field launched with a focused air-coupled transducer, and also with acoustic masks, focusing mirrors, [9][10][11] and Fresnel plates [11][12][13] ), the radiation pattern (i.e., spatial distribution of I) can be manipulated at the air/medium interface. In addition, ultrasound arrays can electronically scan the pump field across the interface.…”
mentioning
confidence: 99%
“…Inspired by the research on subwavelength, defined as less than the incident wavelength, focusing hypothesized by Veselago [1] and demonstrated by Pendry [2], several groups are exploring structures with subwavelength features to focus acoustic waves or to achieve acoustic cloaking. Three dimensional and two dimensional periodic [3][4][5][6][7][8][9][10][11][12][13] and aperiodic [14][15][16] Welter et al recently demonstrated subwavelength focusing of acoustic waves in air using a cylindrical aperiodic structure [19]. Focusing was examined in the frequency range of 80-90…”
Section: )mentioning
confidence: 99%